Three-dimensional Visualization of Dynamic Oscillation of Structural Components Using Inhomogeneous Wireless Sensors. (2017) - Matsumoto, Ai; Saito, Naka; Takamoto, Tatsunao; Nakahata, Kazuyuki
Abstract: A three-dimensional visualization system was developed to investigate the dynamic state of bridge components using portable sensors located at multiple points. The system utilizes wireless data transfer and real-time signal processing for on-site output of the dynamic oscillation of bridge components. Vibrational modes (bending, twisting, and translation) are determined upon excitation by an external load. In this study, a sensor fusion technique was introduced to enhance the accuracy of motion visualization. An angular velocity sensor and an accelerometer were mounted within each sensor box. The same sensor boxes were prepared, and boxes were placed at 12 positions in all. The performance of the system was checked using a mock-up reinforced concrete beam. In cyclic loading tests of the mock-up, variations in the natural vibration frequency and its mode shape were observed. It was shown that disturbance of the initial motion may be used to detect crack initiation, and that changes in the mode shape may be used to detect the location of the damaged area.